Upaya Meningkatkan Hasil Belajar Siswa Kelas Iii Pada Pelajaran Matematika Materi Pecahan Sederhana Melalui Alat Peraga Puzzle - Ester Julinda Simarmata; Rosdiana Samosir; Fitri Almy Tujza; Syahriatul Lisma; Rosdiana Rosdiana; Synta Rinjani Sirait; Supriati Supriati; Suzanna Indra; Sulastri Pasaribu; Sulastri Sulastri (Journal on Education, 2023)
This research aims to evaluate the impact of implementing puzzle learning media in class III Mathematics learning at SD Negeri 091316 Pematang Raya. Using a classroom action research approach, the research was carried out in two cycles with a focus on changing students' attitudes and improving student learning outcomes. The results of the research showed significant changes in attitudes among students during the learning process in cycle 2, while there was an increase in student learning outcomes in cycle 2 compared to cycle 1. Puzzle learning media was chosen as an innovation because it can involve students actively, stimulate patience, dexterity and courage. students in presenting opinions. Data analysis uses quantitative and qualitative approaches with descriptive analysis techniques. The conclusion of this research shows that the use of puzzle learning media can have a positive impact on changing attitudes and improving student learning outcomes. The classroom action research approach can be used as a guide for teachers in improving their learning process. This research contributes to the understanding of the effectiveness of innovative learning media in improving learning at the elementary level.